Tinjauan Yuridis Pemberian Izin Kegiatan Penanaman Modal Dalam Persfektif Otonomi Daerah - Nachrawi, Gunawan; Robekha, Jamiatur; Fitrianingtyas Sukarno, Eins (Fundamental: Jurnal Ilmiah Hukum, 2022)
Local governments (Pemda) are given the authority to regulate and manage their own households according to the principles of autonomy and assistance tasks. laws and regulations governing local governments through the principles of decentralization, deconcentration and co-administration can be used as indicators of the size of the regional authority in regulating and managing their household affairs. The greater the application of the principle of decentralization to the regions, according to Article 11 paragraph 1 of Law Number 32 of 2004, among others, based on externality, accountability and efficiency by taking into account the harmony of relations between government structures. (2) Law Number 32 of 2004 concerning Regional Government states that government affairs under the authority of regional governments consist of mandatory and other matters. Article 13 paragraph 1 point n of Law Number 32 of 2004 states that mandatory affairs under the authority of the provincial government are affairs on a provincial scale which include investment administration services, including across districts/cities. In Article 14 paragraph 1 point n of Law Number 32 of 2004 it is stated that the obligatory affairs to become the authority of the regional government for regencies/municipalities are district/city-scale affairs covering administrative services and investment.